5+y+2y? = 5+3y?
5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
X + 3y - 2y + 3y = X + (3-2+3)y = X + 4y
(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y
It is y+3y-2y = 2y simplified
3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8
If 3y = 12, 2y = 8
Then 3y+1-2y can be simplified to y+1
2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6
-3y + y = -2y
That would depend on the plus or minus value of 3y or maybe an equality is missing none of which have been given.
5y-2y= 3y+2 5y-2y-3y= 2 0y= 2
9y-3y=6y; 6y+2y=8y; so your answer is 8y
It simplifies to: 12x+3y
It is then 2y
4x+3y-2x+y 4x-2x+3y+y 2x+4y Taking out 2 common 2(x+2y) Hence the required answer is 2(x+2y)
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
If you mean: 80 = 3y+2y+4+1 then 80 =5y+5 and so y = 15
10x - 5y + 2x - 3y = 12x - 8y
if you wish to multiply 3y-2y by 3y-y the answer is 2y^2
2y + 1.
5x - 3y -7x + 2y +3x = (5-7+3)x + (-3+2)y = x - y